Tax Regulation Dissemination and Administrative Sanctions as Determinants of Motor Vehicle Tax Compliance: An Empirical Study at UPPD Samsat Banjarmasin II - Muhammad Teguh Nuryadin; Yunida, Riswan; Kelik Hardinto, Raden (International Journal of Economics, Business and Innovation Research, 2025)
The rapid increase in the use of two- and four-wheeled vehicles has significantly expanded the number of registered motor vehicle taxpayers. In this context, effective dissemination of tax regulations and the imposition of administrative sanctions are considered essential strategies to enhance taxpayer compliance and mitigate tax arrears. This study aims to investigate the extent to which tax regulation dissemination and administrative sanctions influence the prevention of motor vehicle tax arrears at UPPD Samsat Banjarmasin II, both individually and concurrently. This research employs a quantitative descriptive approach utilizing multiple linear regression analysis. The sample consists of 100 registered taxpayers in Banjarmasin, selected through stratified judgment sampling. Data were collected through electronically distributed questionnaires using Google Forms.The empirical findings demonstrate that tax regulation dissemination has a significant partial effect on the reduction of motor vehicle tax arrears. Similarly, administrative sanctions exert a significant partial influence on tax arrears prevention. Furthermore, when examined simultaneously, both variables collectively have a significant impact on minimizing the growth of motor vehicle tax arrears at UPPD Samsat Banjarmasin II.